Can the Grain-for-Green Program Really Ensure a Low Sediment Load on the Chinese Loess Plateau?. (October 2019) - Sun, Pengcheng; Wu, Yiping; Yang, Zhifeng; Sivakumar, Bellie; Qiu, Linjing; Liu, Shuguang; Cai, Yanpeng
Abstract: The Chinese Loess Plateau is the most seriously eroded area in the world and contributes the vast majority of the sediment that goes into the Yellow River. Since the 1950s, progressive soil and water conservation measures have been implemented—in particular, large-scale ecological restoration has been ongoing since 1999—resulting in a significant reduction of the sediment load. However, the mechanism of the sediment transport dynamics is not fully understood due to multiple and complicated influencing factors including climate change and human activities (e.g., ecological restoration). A challenging question, then, arises: Is the current low sediment level a "new normal" in this era and in the future? To address this question, we selected a typical loess hilly region where considerable ecological restoration has been implemented, and which is regarded as the site of the first and most representative Grain-for-Green program in the Loess Plateau. We investigated the evolution of discharge–sediment relationships in the past decades (1960–2010) and their association with the soil and water conservation measures in this area. The results showed that there was a distinct change in the regression parameters of the commonly used annual discharge–sediment regression equation—a continuously increasing trend of parameter b and a decreasing trend of parameter a, accompanying the ecological restoration. The increase in exponent b (i.e., a steeper slope) implies a potential lower sediment load resulting from low discharge and a potential higher sediment load resulting from large discharge. This finding may question the new normal of a low sediment level and implies the potential risk of a large sediment load during extremely wet years.